Technical efficiency and total factor productivity of rural banks in Ghana - Eric Fosu Oteng-Abayie (Cogent Economics & Finance, 2017)
This study sought to estimate the level of technical efficiency and total factor productivity of RCBs in Ghana using Stochastic Frontier Analysis (SFA). The total factor productivity (TFP) was decomposed into efficiency change and technical change over the study period. Quarterly data spanning 2009 to 2012 was sourced from the ARB-Apex Bank for a sample of 107 out of 137 RCBs in Ghana. The findings suggested that RCBs have room to improve on their technical efficiency and total factor productivity levels. Technical efficiency change, on average, was the main source of total factor productivity change during the period. The results suggest the shifting of the RCBs production frontier causing improvement in the TFP. The finding implies that efforts to improve efficiency and productivity of RCBs must be focused on improving the operational environment through rigorous efficiency analysis and monitoring by the regulator and management boards. The findings on the relative efficiencies also have implications for investment decision by prospective investors.
Keywords: G20; G21; G28; 330; rural and community banks; productivity; technical efficiency; stochastic frontier analysis (SFA); Ghana